1997
DOI: 10.1177/1359104597022004
|View full text |Cite
|
Sign up to set email alerts
|

A Description and Evaluation of a Community Child Mental Health Service

Abstract: A community-based child mental health service was established for families of preschool children with emotional and behavioural problems in the children, psychosocial problems in the family or parenting difficulties. The intervention was home-based and conducted by health visitors and paediatric community medical officers trained in parent counselling, parenting issues and child behavioural management. The approach was based upon frameworks derived from counselling theory, with the intervention dependent upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 15 publications
1
44
0
Order By: Relevance
“…Studies examining the FP training program have demonstrated its effectiveness in improving practitioner knowledge, skills and qualities (Davis et al, 1997;Papadopoulou et al, 2005). Establishing a working relationship of this nature may help to facilitate change in and by itself but this is unlikely when families face complex difficulties with few immediate resources.…”
Section: Family Partnerships Model and Child Protectionmentioning
confidence: 99%
“…Studies examining the FP training program have demonstrated its effectiveness in improving practitioner knowledge, skills and qualities (Davis et al, 1997;Papadopoulou et al, 2005). Establishing a working relationship of this nature may help to facilitate change in and by itself but this is unlikely when families face complex difficulties with few immediate resources.…”
Section: Family Partnerships Model and Child Protectionmentioning
confidence: 99%
“…However, one way of dealing with waiting lists in one service is to set up a project in another. Davis et al (1997) and Davis and Spurr (1998) studied the effectiveness of a consultation service for parents of children with behaviour problems, which had been set up because of a long waiting list to see clinic-based specialists. They found that, after an average of six sessions in the home, the mothers had developed greater self-confidence through…”
Section: Sigurd Reimersmentioning
confidence: 99%
“…Later research showed 'The more deprived and initially less well-supported families derived the greatest benefits' the programme to be effective with parents of preschool children with behaviour problems in reducing the severity of the identified problems, increasing parental self-esteem, decreasing levels of parental stress and emotional difficulties, improving positive parental constructions of their children and improving the home environment and child behavioural problems (Davis and Spurr, 1998). There was also evidence to show that the Parent Adviser Programme was both acceptable to non-mental health professionals, including health visitors, and effective in preparing them to work with a range of psychosocial problems (Davis et al, 1997).…”
Section: Working In Partnership With Parents-the Parent Adviser Progrmentioning
confidence: 95%
“…The programme is based on the assumption that parents and children are actively engaged in making sense of their world by anticipating events, and that they do so by developing a unique and complex system of constructs. Change and adaptation, especially in the face of problems, requires the exploration and modification of these constructions, and particularly those relating to their perceptions of themselves, their partners, their children and all other major figures in their lives, including those who offer help (Davis et al, 1997). It is also assumed that the process of helping involves a number of stages, the first and most important of which is the development by the helper of an appropriate relationship with the parents.…”
Section: Working In Partnership With Parents-the Parent Adviser Progrmentioning
confidence: 98%